2011
DOI: 10.1186/1756-9966-30-75
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol promotes breast cancer cell invasion by regulating the Nm23-ITGA5 pathway

Abstract: BackgroundAlcohol consumption is an established risk factor for breast cancer metastasis. Yet, the mechanism by which alcohol promotes breast cancer metastases is unknown. The ability of cancer cells to invade through tissue barriers (such as basement membrane and interstitial stroma) is an essential step towards establishing cancer metastasis. In the present study, we identify and examine the roles of two genes, Nm23 and ITGA5, in alcohol-induced breast cancer cell invasion.MethodsHuman breast cancer T47D cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Alcohol-induced mobility may result from the interaction with the extracellular matrix (EMC) and reorganization of the cytoskeleton system [38, 39]. Alcohol also increases the invasive potential of breast cancer cells [37, 4042]. The increased invasion is likely mediated by the enhanced ability of breast cancer cells to degrade the EMC, in which matrix metalloproteinases (MMPs) play an important role [40, 41].…”
Section: Alcohol-induced Aggressiveness Of Breast Cancermentioning
confidence: 99%
“…Alcohol-induced mobility may result from the interaction with the extracellular matrix (EMC) and reorganization of the cytoskeleton system [38, 39]. Alcohol also increases the invasive potential of breast cancer cells [37, 4042]. The increased invasion is likely mediated by the enhanced ability of breast cancer cells to degrade the EMC, in which matrix metalloproteinases (MMPs) play an important role [40, 41].…”
Section: Alcohol-induced Aggressiveness Of Breast Cancermentioning
confidence: 99%
“…Ethanol activates MMP-2 production by fibroblasts in a dose-dependent manner and culture medium collected from ethanol-exposed fibroblasts significantly alters the invasive behavior of breast cancer cells and mammary epithelial cells [128]. In addition, a recent in vitro study showed that ethanol promotes the adhesion of breast cancer cells to fibronectin, an important component of the extracellular matrix through suppression of the Nm23 meta-static suppressor gene and subsequent enhancement of fibronectin receptor ITGA5 expression [129]. Ethanol stimulates migration and invasion of breast cancer cells [129], particularly those overexpressing HER2 [130].…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…In a subset of breast cancers, overexpression of Steroid Receptor Coactivator-1 (SRC-1) was associated with an upregulation of α5β1 integrin and promotion of α5β1 integrin-dependent cell adhesion and migration [84]. Inverse relationship between α5β1 integrin expression and tumor suppressors expression such as nischarin [85], metastasis suppressors such as Nm23 [86] or epithelial cell-cell adhesion marker such as E-cadherin [87] were reported and associated with impact on breast cell tumorigenic potential. Loss of E-cadherin was also achieved through stimulation of breast cancer cells by angiopoietin-2 which stimulated cell migration through an α5β1 integrin-dependent way [88].…”
Section: Integrin α5β1 In Solid Tumorsmentioning
confidence: 99%